Maternal Vocal Interactions with Infants: Reciprocal Visual Influences. Issue 3 (14th October 2015) - Trehub, Sandra E.; Plantinga, Judy; Russo, Frank A.
Abstract: The present study examined the influence of infant visual cues on maternal vocal and facial expressiveness while speaking or singing and the influence of maternal visual cues on infant attention. Experiment 1 asked whether mothers exhibit more vocal emotion when speaking and singing to infants in or out of view. Adults judged which of each pair of audio excerpts (in view, out of view) sounded more emotional. Face‐to‐face vocalizations were judged more emotional than vocalizations to infants out of view. Moreover, mothers smiled considerably more while singing than while speaking to infants. Experiment 2 examined the influence of video feedback from infants on maternal speech and singing. Maternal vocalizations in the context of video feedback were judged to be less emotional than those in face‐to‐face contexts but more emotional than those in out‐of‐view contexts. Experiment 3 compared six‐month‐old infants' attention to maternal speech and singing with audio‐only versions or with silent video‐only versions. Infants exhibited comparable attention to audio‐only versions of speech and singing but greater attention to video‐only versions of singing. The present investigation is unique in documenting the contribution of infant visual feedback to maternal vocal emotion in contexts that control for infants' presence, visibility, and proximity.